Measurement of endogenous lithium levels in serum and urine by electrothermal atomic absorption spectrometry: A method with potential clinical applications - Miller, Nancy L.; Durr, Jacques A.; Alfrey, Allen C. (Analytical biochemistry, 1989)
A highly sensitive flameless atomic absorption method has been adapted for the determination of endogenous trace lithium levels in serum and urine. With ammonium nitrate as the only matrix modifier, serum levels of Li as low as 0.03 μmol/liter are measured accurately and there is no requirement for standard additions. The need for background correction during analysis was clearly established, and tungsten and Zeeman-effect background corrections were compared. The tungsten correction offered superior sensitivity and linearity of standards. Recoveries in urine and serum average 94.8 ± 7.7 and 95.3 ± 6.1% (±SD), respectively. The endogenous serum Li levels were 0.16 ± 0.08 μmol/liter for normal subjects dwelling in the Denver metropolitan area. The mean 24-h excretion rate was 5.24 ± 1.4 μmol/day. The mean fractional excretion of endogenous Li (clearance Li/clearance creatinine) was 23.2 ± 3.0%, a value similar to values published for exogenously administered Li and measured by conventional methods.